Microfibrillar‐associated protein 4 in serum is associated with asthma in Danish adolescents and young adults. Issue 3 (28th June 2019) - Hoffmann‐Petersen, Benjamin; Suffolk, Raymond; Petersen, Jens Jakob Herrche; Petersen, Thomas Houmann; Arendt, Kirsten; Høst, Arne; Halken, Susanne; Sorensen, Grith Lykke; Agertoft, Lone
Abstract: Background: Microfibrillar‐associated protein 4 (MFAP4) is an extracellular matrix protein belonging to the fibrinogen‐related protein superfamily, which plays multifaceted roles in innate immunity and normal endothelial function. It has been proposed that MFAP4 promotes the development of asthma in vivo and proasthmatic pathways of bronchial smooth muscle cells in vitro. The aim of this study was to investigate the significance of serum MFAP4 in adolescents and young adolescents with persistent asthma. Methods: Prospective, observational study including adolescents and young adults (age 11‐27 years) previously diagnosed with asthma during childhood 2003 to 2005 (0‐15 years) at the four pediatric outpatient clinics in the Region of Southern Denmark (n = 449). Healthy controls were recruited at follow‐up (n = 314). Detection of serum MFAP4 was performed by AlphaLISA technique. Results: Current asthma was associated to a 14% higher mean level of serum MFAP4 compared with controls (exp β 1.14, 95% confidence intervals [CI], 1.05‐1.23) and a 6% higher mean level compared with subjects with no current asthma (exp β 1.06, 95% CI, 0.99‐1.13). No association was found at follow‐up between serum MFAP4 and self‐reported atopic symptoms (other than asthma), Asthma Control Test‐score, fractional exhaled nitric oxide (FeNO), nor to flow rate at 1 second, forced vital capacity, and forced expiratory flow 25% to 75%, response to short‐acting beta 2 agonist or mannitol. Conclusions: We found a significantly higher mean level of serum MFAP4 in adolescent and young adults with mild to moderate asthma compared with healthy controls but no association to FeNO and lung function nor to the response to short‐acting beta 2 agonist or mannitol. The result supports the hypothesis that MFAP4 plays a role in the pathogenesis of asthma although the marker did not demonstrate any obvious potential as an asthma biomarker in adolescents and young adults with asthma. To understand the possible proasthmatic functions of MFAP4, further investigation in specific asthma phenotypes and the underlying molecular mechanisms is warranted. Abstract : This is the first clinical study investigating the significance of serum microfibrillar‐associated Protein 4 (MFAP4) in adolescents and young adults with asthma. The study reveals an association between the extracellular matrix protein MFAP4 and current asthma in a comprehensively characterized population of adolescents and young adults previously diagnosed with asthma during childhood. The study supports previous findings from experimental in vitro and in vivo studies hypothesizing that MFAP4 plays a role in the pathogenesis of asthma.